The adsorption of iron (III) ions to Schizomeris leibleinii - Özer, Ayla; Özer, Dursun; Ekiz, H. Ibrahim; Aksu, Zümriye; Kutsal, Tülin; Ça?lar, Arif (My University, 1997)
In this report, the adsorption of iron (III) ions to Schizomeris leibleinii, a green algae, was studied in an agitated batch reactor. The effects of the initial pH, temperature, initial metal ion concentration and microorganism concentration on the initial adsorption rate were investigated and the best adsorption conditions were found to be 2.5, 30 °C, 100 mg/L and 0.50 g/L, respectively. Moreover, the agitation rate did not affected the initial adsorption rates. The Freundlich and Langmuir adsorption isotherms were developed at different initial pH and temperature values. The analysis of the experimental data obtanied at the optimal adsorption condition indicated that Freundlich isotherm model was a better fit to the experimental data than that of langmuir.
Demir (III) iyonlarinin Schizomeris leibleinii'ye adsorpsiyonu
Keywords: Adsorption isotherms; Heavy metal adsorption; Schizomeris leibleinii